130 Valvular 18F-Fluorodeoxyglucose Uptake Predicts Disease Progression and Clinical Outcome in Patients with Aortic Stenosis. (6th June 2015) - Jenkins, William; Vesey, Alex; Shah, Anoop; Pawade, Tania; Chin, Calvin; Fletcher, Alison; Beek, Edwin van; Boon, Nicholas; Rudd, James; Newby, David; Dweck, Marc
Abstract : Background: Inflammation is a key process in the pathogenesis of Aortic valve disease. 18F-Fluorodeoxyglucose (18F-FDG) is an established positron emission tomography (PET) radiotracer that has become recognised as a marker of inflammatory activity in the vasculature and aortic valve. We sought to assess its ability to predict disease progression and clinical outcome in patients with aortic stenosis. Methods and results: PET and computed tomography (CT) using 18F-FDG (200 MBq) was performed in 121 volunteers (72 ± 8 years, 68% men) with and without aortic valve disease (20 controls; 20 aortic sclerosis; 25 mild, 33 moderate, and 23 severe aortic stenosis). Disease progression was assessed at 1 and 2 years using CT aortic valve calcium score and echocardiography. The primary clinical outcome endpoint was a composite of cardiovascular death and aortic valve replacement (AVR). Aortic valve calcium score increased by 61 (5–226) AU/year and aortic valve mean gradient increased by 0.7 (-0.2–2.9) mmHg/year. Baseline valvular 18F-FDG uptake (corrected for blood pool activity and valve area) correlated with the rate of progression in aortic valve calcium score (r = 0.43, p = 0.001). Modest correlations were observed between 18F-FDG valvular uptake and echocardiographic measures of disease progression (mean aortic valve gradient, r = 0.30, p = 0.002; peak aortic jet velocity, r = 0.28, p = 0.005). After a median of 1, 232 (IQR 1148–1322) days, 23 patients had undergone AVR whilst 5 had died from a cardiovascular cause. After age and sex-adjustment, valvular 18F-FDG uptake was an independent predictor of clinical outcome (HR 1.59 (1.21–2.09), p = 0.002). Conclusion: Valvular 18F-FDG uptake predicts progression in aortic valve calcification and stenosis, and is associated with an adverse clinical outcome.